Interagency collaboration and identifying mental health needs in child welfare: Findings from Los Angeles County. (June 2015) - He, Amy S.; Lim, Caroline S.; Lecklitner, Greg; Olson, Adrienne; Traube, Dorian E.
Abstract: Research has indicated that disparities between the need for and receipt of mental health services are in part due to challenges in identifying mental health problems in this population. Interagency collaboration between the child welfare system (CWS) and mental health organizations shows promise in circumventing these challenges. To this end, Los Angeles County's Department of Children and Family Services (DCFS) and Department of Mental Health (DMH) engaged in interagency collaborative efforts that included the development of a collaborative model detailing steps for systematic screening, assessment, referral, and continuum of care for mental health needs of DCFS-involved children. DCFS and DMH also developed a uniform agency mental health screening tool to be used by the DCFS staff to enhance identification of needs and expedite services for CWS-involved children at risk of mental health problems. This article describes the processes of interagency collaboration between DCFS and DMH, development of a uniform agency mental health screening tool, and demographic descriptors of an ethnically diverse cohort of CWS-involved children who received the mental health screening protocol (N = 4694) between 2011 and 2012. Findings indicate that collaborative efforts between DCFS and DMH facilitated the mental health screening of a large cohort of CWS-involved children, which resulted in the detection of need and referral for services. Highlights: We describe collaboration between child welfare and mental health agencies in Los Angeles County. We depict the development of a uniformed agency mental health screening tool. A description of the children screened is provided. Collaboration facilitated mental health assessment of child-welfare involved youth.